Small deviations of solutions of stochastic differential equations in tube domains - Gasanenko, V. A. (Ukrains’kyi Matematychnyi Zhurnal, 1997)
We present an algorithm for the determination of a complete asymptotic decomposition of the sojourn probability of a one-dimensional diffusion process in a thin domain with curvilinear boundary.